The Use of Preoperative Psychological Evaluations to Predict Spinal Cord Stimulation Success: Our Experience and a Review of the Literature. Issue 4 (28th April 2016) - Fama, Christopher A.; Chen, Nita; Prusik, Julia; Kumar, Vignessh; Wilock, Meghan; Roth, Steven; Pilitsis, Julie G.
Abstract : Background: Pre‐operative psychological assessment is commonly used to assess patients for spinal cord stimulation (SCS). Though often times mandated by insurance, its value is frequently questioned. Methods: We review the literature on the predictive value of psychological testing prior to SCS and retrospectively examine our prospective database of SCS patients. We examine associations of Minnesota Multiphasic Personality Inventory (MMPI), Beck Depression Inventory (BDI), and Pain Catastrophizing Scale (PCS) findings and outcomes on the visual analog scale (VAS), McGill Pain Questionnaire – Short Form (MPQ), and Oswestry Disability Index (ODI) at 6 and 12 months post‐implantation. Results: The nine studies examining psychological predictors of SCS outcomes collectively showed that substance abuse or feelings of demoralization or less joy correlated with worse outcomes. Though not statistically significant, our data show that at one year follow‐up, patients without psychiatric disorders improved 1.5 times as much on ODI and 2.4 times as much on PCS as compared to patients with psychiatric disorders. Further, depressed patients concurrently treated with anti‐depressants had greater improvement in BDI than non‐medicated depressed patients ( p = 0.009). We develop a tool for pain psychologists based on the existing literature to aid in identifying possible concerns and treating these patients peri‐operatively. Discussion: The predictive value of psychological testing depends on which psychiatric factors are used and which outcomes are measured. The predictive capacity of psychological indications can be used to holistically treat patients, specifically to recommend psychiatric medication and consulting to supplement SCS treatment as needed.